The Effect of Gamification and Technology Acceptance Model (TAM) towards Intention to Buy in Online Travel Agent Traveloka - Fenny Natasya; Clarissa L. Susilo (Journal of Management and Administration Provision, 2022)
These days, it can be seen that the world’s population keeps on rising. This growth in population has different effect in different sectors, including the tourism sector – especially in the accommodation and transportation sectors. In order to fulfill this demand, travel agent emerge as an organization who helps consumer during their trip. With the emerge of digitalization in every single aspect of lives, these days people prefer to use an Online Travel Agent (OTA) to help them with their trip. The study's objective is to determine if the online travel agency Traveloka's use of gamification and the Technology Acceptance Model influences consumers' desire to make a purchase. SPSS was used for data analysis in this study. Research shows that gamification has a sizeable impact on purchase desire in the online travel agency Traveloka. Evidently, TAM also has a substantial impact on consumers' desire to make a purchase through OTA Traveloka.